THE IMPACT OF TRAINING AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE IN PT TELKOM AKSES - Syifaul Hamam (Publikasi Indonesia, 2023)
The title of this research is the impact of training and organizational culture on employee performance through employee engagement as an intervening variable in PT Telkom Akses Yogyakarta. The study aims to determine the influence of employee engagement mediation in the relationship between organizational culture and training on employee performance. This research is performed quantitatively and uses questionnaires as data collection methods. Population of 339 employees. Research samples used as much as 80 employees. Therefore, sampling uses the slovin’s formula method. Methods of research analysis using T-Test, simple and multiple linear regression analysis. The results showed that training and organizational culture were positively and significantly influential for employee engagement, training and organizational culture were positively and significantly impacted by employee performance. There is a significant mediation influence from employee engagement in organizational cultural relationships to employee performance. There is a significant mediation influence of employee engagement on the training relationship to the employee's performance.